Jamnagar Petrochemical Complex - Reliance Industries Limited (2022)
Jamnagar Petrochemicals complex and bulk of integrated refinery complex commissioned. • It is the world’s largest grassroots integrated single-site refinery complex • India’s largest port with capacity of 50 million TPA • World’s largest PX plant of 1.4 million tonnes per annum • World’s largest PP plant of 0.6 million tonnes per annum • Captive power plant of over 1,000 MW • World-class product handling, storage, and dispatch facilities